First-principle study of structural, electronic and magnetic properties of chromium-doped magnesium selenide: An interesting demonstration of half-metallic ferromagnetism. (May 2015) - Rashid, Muhammad; Ahmad, S.A.; Abo, Gavin S.; Imran, Muhammad; Hussain, Fayyaz; Noor, N.A.; Karim, Altaf
Abstract: The structural, electronic and magnetic properties of Cr-based MgSe in zinc blende phase have been investigated by employing the full-potential linear augmented plane waves plus local orbitals (FP-LAPW+lo) method within the spin-polarized density functional theory (DFT). According to our findings, Mg1− x Cr x Se exhibits a half-metallic characteristic, where the ferromagnetic state is more favorable than the antiferromagnetic state. The band structure results of half-metallic Mg1− x Cr x Se system for x =0.25, 0.50 and 0.75 show 100% spin-polarization at the Fermi level ( E F ). The total magnetic moment is 4 μ B which is mainly due to the Cr-3 d states at the Fermi level ( E F ). Our results indicate the presence of small magnetic moments arising from the other non-magnetic atoms as well. We also calculated the spin dependent charge densities to understand the bonding nature of the system.